Programas de difusión tributaria y cumplimiento de obligaciones tributarias en los contribuyentes del Mercado Jorge Samuel Chávez Sibina San Juan 2024 - Lopez Laulate, Rosa Amelia (2025)
The general objective of this research study was to determine the relationship between tax dissemination programs and compliance with tax obligations in taxpayers in the Jorge Samuel Chávez Sibina, San Juan 2024 market. To do so, a basic type study was chosen, with a descriptive correlational approach and a non-experimental design. The sample consisted of 102 merchants, who were given a questionnaire to obtain the necessary data. The results allowed us to conclude that tax dissemination programs are considered regular by 29% of merchants. This is because, although on some occasions they have attended talks on tax issues in the market jurisdiction, on others they have not received sufficient information on the matter. Likewise, it was determined that compliance with tax obligations is also rated as regular by 29%. This evaluation is based on the intermittent updating of information in the Tax Administration and the occasional issuance of referral guides when appropriate. Finally, the relationship between tax awareness programs and tax compliance was determined, corroborated by a Spearman Rho coefficient of 0.848 and a bilateral significance of 0.000.